Peranan Kekristenan dalam Menghadapi Masalah Ekologi - Marianus Patora (JURNAL TERUNA BHAKTI, 2019)
Ecological issues are now very worried man on the planet. Deforestation, soil excavation, burning forests, polluted rivers, sewage plant that is not well controlled, until the waste can not control it advanced technology. All this makes the concerns are very exceptional in all areas of the human race. There have been many non-governmental organizations and governments are fighting to awaken humanity of the dangers of ecological destruction of the earth. In the spiritual realm, the role of religious communities are required to be actively involved to become agents of change, with a mouthpiece for the creation of the world's ecological sistima good and true. This also applies to Christians. What and how the role of Christians in the face of this ecological issues? This paper inspires Christians to engage actively to preserve the universe, such as what is contained in the word of God or the Bible. Abstrak Persoalan Ekologi saat ini sudah sangat mencemaskan manusia di planet ini. Pengrusakan hutan, penggalian tanah, pembakaran hutan, sungai-sungai yang tercemar, limbah pabrik yang tidak dikontrol dengan baik, sampai dengan tidak dapat dikontrolnya limbah teknologi canggih. Semua hal ini membuat keprihatianan yang sangat luar biasa di segala bidang umat manusia. Sudah banyak lembaga swadaya masyarakat dan pemerintah yang berperang untuk menyadarkan umat manusia akan bahaya rusaknya ekologi bumi ini. Dalam bidang spiritual, peranan umat beragama dituntut untuk terlibat aktif untuk menjadi agen perubahan, dengan menjadi corong bagi terciptanya sistima ekologi dunia yang baik dan benar. Hal ini juga berlaku bagi orang Kristen. Apa dan bagaimana peranan orang Kristen dalam menghadapi isu-isu ekologi ini? Tulisan ini menggugah orang Kristen untuk terlibat aktif untuk menjaga kelestarian alam semesta, seperti apa yang termaktub dalam firman Tuhan atau Alkitab.